(untitled) (JOURNAL OF UNIVERSITY OF BABYLON for Pure and Applied Sciences, 2018)
Objective: Silica nanoparticles have been discovered to exert cytotoxicity in normal and cancerous human cells. Therefore, this study is aimed to evaluate the cytotoxic effect of silica nanoparticle on some tumor cell lines. Materials and Methods: Six concentrations (100,200,400,600,800, and1000 µg/ml) of silicon oxide SiO2nanoparticles (SONPs)with particle size 20-30 nm were prepared and their cytotoxic effect was tested on Hela, RD and ANM3 cancer cell lines as well as REF normal cell line as a control for 24 and 48 hr by using MTT assay to estimate the optical density (OD) of cell growth at wave length 500nm. Results: All tumor cell lines (RD, HeLa, and AMN3) demonstrated significant inhibition in the cell growth index (GI%) after 24 and 48 hr exposure to all concentrations of SONPs, however the GI% of Ref cell showed non-significant change after both incubation periods of treatment. On the other hand, only RD cell line showed significant negative correlation (r=- 0.8178, P=0.047) between GI% and the concentration of SONPs after 24 hr exposure, while those HeLa, AMN3,and REF cell lines showed non-significant correlation whether after 24 hr or 48 hr of treatment. Conclusion: The SONP per se at diameter 20-30 nm revealed significant cytotoxic effect based on MTT assay in different tumor cell lines, and the magnitude of their cytotoxic effect is dose-independent in the majority of cell lines which indicated that they are acting in cell type-dependent manner. Therefore, pathways by which SONPs induced their cytotoxic effect in tumor cells need further investigation.